The Development of Business Based on Sharia to Achieve Common Profit and Community Welfare at Islamic Boarding School Azkal Azkia Liddarain NW - Mustakim, Mustakim; Lasmawan, I Wayan; Suastika, I Nengah (LP2M STIT Palapa Nusantara, 2024)
The objective of this research is: 1) To explore the implementation process of business based on syaria development at Islamic Boarding School Azkal Azkia Liddarain NW; 2) To analyze the impact of the business based on syaria model on the community welfare around Islamic Boarding School Azkal Azkia Liddarain NW; and 3) To assess the contribution of business based on syaria to economic profit and social development at Islamic Boarding School Azkal Azkia Liddarain NW. The research method used a mixed-methods approach, combining qualitative and quantitative aspects. Through this mixed-methods approach, several data collection techniques were applied, including Interviews, Surveys, Case Studies, Financial Analysis, Focus Group Discussions (FGD), and Document Content Analysis. Data analysis techniques involved an integrated approach that combined qualitative and quantitative analysis methods. 1) Qualitative Analysis, including: a) Interviews, b) Focus Group Discussions, and c) Document Content Analysis. 2) Quantitative Analysis, including: a) Surveys, and b) Financial Analysis. 3) Integration and Conclusion Drawing, including: a) Comparing Qualitative and Quantitative Data, and b) Drawing Conclusions and Recommendations. The results show that 1) The process of developing business based on syaria at Islamic Boarding School Azkal Azkia Liddarain NW has successfully achieved common profit between the pesantren and the community. The implementation of business based on syaria business based on syaria mechanisms, support from economic and social factors, and the positive impact on community welfare are integral components in achieving sustainable business goals; 2) The implementation of the business based on syaria model at Islamic Boarding School Azkal Azkia Liddarain NW has a positive impact on the welfare of the surrounding community. In addition to improving the economic aspect, this business model also plays a role in empowering the economy and social development of the community. This conclusion indicates that business based on syaria can be an effective instrument in enhancing holistic community welfare; and 3) Business based on syaria at Islamic Boarding School Azkal Azkia Liddarain NW makes a positive contribution to the improvement of economic profit and social development in the surrounding community. The application of Sharia principles in business activities brings broader positive impacts, creating an inclusive and sustainable environment for the Islamic boarding schools and the local community. This conclusion emphasizes the importance of business based on syaria in empowering the economy and promoting social development at the local level.